This preview shows page 1. Sign up to view the full content.
Unformatted text preview: partial derivative of f (Exercise 6 ): g ( t ) = f x ( x + t x,y + y ) x. Thus, we can apply the Mean Value Theorem to conclude that there is a value t = t 1 between 0 and 1 for which g (1) g (0) = g ( t 1 ) . Letting t 1 x = 1 , we can write f ( x + x,y + y ) f ( x,y + y ) = g (1) g (0) = g ( t 1 ) = f x ( x + 1 ,y + y ) x where | 1 | | x | ....
View Full Document
This note was uploaded on 10/20/2011 for the course MAC 2311 taught by Professor All during the Fall '08 term at University of Florida.
- Fall '08